2017
DOI: 10.1089/pho.2016.4227
|View full text |Cite
|
Sign up to set email alerts
|

Significant Improvement in Cognition in Mild to Moderately Severe Dementia Cases Treated with Transcranial Plus Intranasal Photobiomodulation: Case Series Report

Abstract: Objective: This study investigated whether patients with mild to moderately severe dementia or possible Alzheimer's disease (AD) with Mini-Mental State Exam (MMSE) Baseline scores of 10–24 would improve when treated with near-infrared photobiomodulation (PBM) therapy. Background: Animal studies have presented the potential of PBM for AD. Dysregulation of the brain's default mode network (DMN) has been associated with AD, presenting the DMN as an identifiable target for PBM. Materials and methods: The study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
203
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(213 citation statements)
references
References 36 publications
6
203
0
4
Order By: Relevance
“…Replicating this alleviated AD phenotype in other preclinical models will be our next step to support clinical investigations. It is however worthy of note to acknowledge that multiple studies have demonstrated that transcranial PBM is safe and well tolerated [7,[53][54][55] and clinical investigations have been already reported [10,12]. Finally, the hypothesis that a dual mechanism of action is involved opens new perspectives for the treatment of AD by widening the therapeutic approach limited up to now by a too reductionistic logic.…”
Section: Discussionmentioning
confidence: 99%
“…Replicating this alleviated AD phenotype in other preclinical models will be our next step to support clinical investigations. It is however worthy of note to acknowledge that multiple studies have demonstrated that transcranial PBM is safe and well tolerated [7,[53][54][55] and clinical investigations have been already reported [10,12]. Finally, the hypothesis that a dual mechanism of action is involved opens new perspectives for the treatment of AD by widening the therapeutic approach limited up to now by a too reductionistic logic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed on healthy volunteers have showed that LLLT can improve human cognitive and emotional brain functions . Similarly, a single‐blind pilot trial on 19 patients with mild cognitive impairment has reported a significant memory improvement and cognitive function after 12 weeks of LLLT treatment .…”
Section: Low‐level Laser Therapymentioning
confidence: 99%
“…This approach consists in illuminating large volume of tissues with red or near infrared light to stimulate non-specifically the cells via mechanisms that are thought to involve absorption by cytochrome-oxydase and further activation of the mitochondria metabolism. The technique is under active review for use in a vast range of brain diseases including stroke, traumatic brain injury, neurodegenerative diseases, where the non-specific optical stimulation of the cortical tissue was shown in mice models to lead to transient increase of ATP, decrease of inflammatory markers and -in some studies-cognitive improvement (reviews in [17,18] and first studies in humans of the use of PBM to alleviate Alzheimer's disease symptoms in [19]). …”
Section: Introductionmentioning
confidence: 99%